Tissue eosinophil level as a predictor of control, severity, and recurrence of Chronic Rhinosinusitis with Nasal Polyps - Vizcarra-Melgar, Julissa; Sánchez-Gómez, Serafín; López-González, Nuria; Moreno-Luna, Ramón; González-García, Jaime; Maza-Solano, Juan (Frontiers in Allergy, 2025)
IntroductionThe histopathologic study of nasal polyps establishes endotype features of chronic rhinosinusitis (CRS). A tissular eosinophil count greater than 10 per high power field (HPF) classifies this condition as type 2 inflammation. Blood and mucosal eosinophils are suggested as biomarkers of severity and control of CRS. Additionally, a tissular eosinophil count greater than 55 per HPF has been related to a high risk of recurrence in the Asian population. Our study aims to determine whether tissue eosinophil count is associated with the control, severity, and recurrence of Chronic Rhinosinusitis with Nasal Polyps (CRSwNP).MethodsAn observational study of patients with CRSwNP who underwent nasal mucosa biopsy was conducted between June 2021 and November 2023. Histopathologic features, asthma control, CRSwNP control and severity according to the POLINA consensus, quality of life parameters, recurrence of CRSwNP, and laboratory markers were recorded and compared with the tissular eosinophil count.ResultsA total of 108 cases were included. The majority (70.4%) had concomitant asthma, with 31.5% of the cases having well-controlled disease. Most patients had uncontrolled (57.4%) and severe (62%) CRSwNP. Fifty-four cases underwent surgery and 43.5% experienced recurrence. More than half had a SNOT-22 score greater than 50 points. Eighty-one percent of patients had a tissular eosinophil count greater than 10 per HPF, and 60.2% had blood eosinophilia greater than 0.3×103. Blood eosinophilia was related to CRSwNP severity and control. No significant differences were found between tissue eosinophil count and the severity, control, and recurrence of CRSwNP.ConclusionTissue eosinophil levels were not a marker of control, severity, and recurrence of CRSwNP in our data. Blood eosinophil levels, however, were a marker of CRSwNP control and severity.